2007
DOI: 10.1200/jco.2006.08.4103
|View full text |Cite
|
Sign up to set email alerts
|

Site of Oncologic Specialty Care for Older Adolescents in Utah

Abstract: The referral of adolescents with cancer to a pediatric oncology center diminishes greatly with age, and is moderately influenced by diagnosis and minimally by distance from center. Further study should investigate reasons for referral patterns, and impact on outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 20 publications
0
107
0
Order By: Relevance
“…Studies have estimated that approximately twothirds of 15-to 19-year-olds are never seen at pediatric centers. 4,11,12 In a population-based cancer registry study, Albritton et al 4 found that, whereas nearly all children under age 10 were seen at pediatric centers, the rate dropped to 34% between 15 and 19 years of age. Furthermore, only 40% of these AYAs were seen at academic sites; 47% were seen at community American College of Surgeons-accredited cancer centers, and 13% were never seen at American College of Surgeons centers.…”
Section: Where Are Ayas With Cancer Currently Being Seen?mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have estimated that approximately twothirds of 15-to 19-year-olds are never seen at pediatric centers. 4,11,12 In a population-based cancer registry study, Albritton et al 4 found that, whereas nearly all children under age 10 were seen at pediatric centers, the rate dropped to 34% between 15 and 19 years of age. Furthermore, only 40% of these AYAs were seen at academic sites; 47% were seen at community American College of Surgeons-accredited cancer centers, and 13% were never seen at American College of Surgeons centers.…”
Section: Where Are Ayas With Cancer Currently Being Seen?mentioning
confidence: 99%
“…3 In part because only one-third of 15-to 19-year-olds are seen at pediatric centers, 4 the CT participation for that age group has usually been approximately one-quarter to one-half the rate of that in younger children. 1,4,5 At pediatric oncology centers, the rate of CT enrollment of AYAs is lower than for younger patients, but it is still higher than the percentage enrolled in trials when treated at nonpediatric cancer centers.…”
Section: Where Are Cts Open For Ayas?mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a substantial number of AYA patients with pediatric malignancies are not being treated at pediatric cancer centers. 22,42,43 The treatment and appropriate location of care vary with the type of cancer as well as with the availability of family, community, and institutional support. 8,44 Most importantly, AYA patients should be evaluated at medical centers with extensive experience in treating cancer in this patient population and at centers that have access to supportive care services (psychosocial/educational support and fertility preservation) specific to the AYA population as well as to medical subspecialty services appropriate to the cancer diagnosis, such as orthopedic surgeons with experience in limb-sparing surgery for patients with extremity sarcomas.…”
Section: Age-appropriate Carementioning
confidence: 99%
“…Recent evidence suggests that most newly diagnosed oncology patients .15 years of age are being treated at community oncology facilities instead of NCI-designated comprehensive cancer centers that typically offer the most clinical trials. 15,16 Studies have shown that when referred to tertiary care centers, AYA patients are much more likely to enroll in clinical trials if treated by a pediatric oncologist rather than an adult oncologist. 10 Yet, of adolescents with cancer treated in Ohio, only 36% of 17-year olds and 23% of 18-year olds were treated by pediatric oncologists compared with 76% of 15-year olds.…”
Section: Dovepressmentioning
confidence: 99%